Parental mentalizing as a key resource for difficult transitions - Taubner, Svenja (Attachment & human development, 2020)
This commentary on Ruiz et al.’s study focuses on the relevance of parental mentalizing for child development within a transactional framework. This view takes into account what kind of challenges in the parent, in the infant, or in the interaction have effects on child development and if this mediated by parental mentalizing. Differences between maternal and paternal mentalizing seem unrelated to the general level of reflective functioning but strongly influenced by social roles of parents. However, more sophisticated measures of mentalizing are needed to better understand subtle problems with regard to a dimensional and multifaceted model of mentalizing as well as interactional processes. To master the transition to parenthood in challenging circumstances such as preterm birth, it would be especially valuable to know if one parent’s lower mentalizing can be counterbalanced by higher mentalizing in the other parent.
Published online: 06 Mar 2019
Gesehen am 17.01.2020